Toxoplasma GRA16 attenuates Tau hyperphosphorylation and enhances autophagy in thrombin-treated HT-22 hippocampal neuronal cells - Seung-Hwan Seo; Do-Won Ham; Ji-Eun Lee; Eun-Hee Shin (Scientific Reports)
Abstract This study investigated whether Toxoplasma gondii-derived dense granule protein 16 (GRA16) modulates tau protein to attenuate tau hyperphosphorylation and promotes autophagy to facilitate the removal of tau aggregates. HT-22 murine hippocampal neuronal cells were treated with thrombin to induce rapid hyperphosphorylations and tau aggregation. Thrombin increased hyperphosphorylated tau protein levels and activated NF-κB, contributing to tau pathology and neuroinflammation. NF-κB activation increased apolipoprotein E (APOE) expression and decreased forkhead box O3A (FOXO3A) expression, a factor involved in autophagy regulation, consequently limiting the expression of autophagy-related genes directly regulated by FOXO3A. Meanwhile, in GRA16-transfected HT-22 cells treated with thrombin, GRA16 upregulated proteins involved in tau dephosphorylation but downregulated protein involved in tau phosphorylation. Moreover, GRA16 inhibited thrombin-induced NF-κB activation and increased FOXO3A levels, thereby enhancing the expression of autophagy-related genes, including those directly regulated by FOXO3A. GRA16 enhanced intracellular autophagic flux and inhibited tau hyperphosphorylations in thrombin-treated HT-22 cells, as evidenced by increased autophagic fluorescence and significant reductions in phosphorylated tau protein levels and fluorescence intensity. These findings suggest that GRA16 possesses therapeutic potential in tauopathies by enhancing tau dephosphorylation and autophagy-mediated tau clearance, establishing a conceptual foundation for developing new therapeutic approaches targeting tau pathology.